Isolation and Characterization of Three New Monoterpene Synthases from Artemisia annua - Ruan, Ju-Xin; Li, Jian-Xu; Fang, Xin; Wang, Ling-Jian; Hu, Wen-Li; Chen, Xiao-Ya; Yang, Chang-Qing (Frontiers in Plant Science, 2016)
Artemisia annua, an annual herb used in traditional Chinese medicine, produces a wealth of monoterpenes and sesquiterpenes, including the well-known sesquiterpene lactone artemisinin, an active ingredient in the treatment for malaria. Here we report three new monoterpene synthases of A. annua. From a glandular trichome cDNA library, monoterpene synthases of AaTPS2, AaTPS5 and AaTPS6, were isolated and characterized. The recombinant proteins of AaTPS5 and AaTPS6 produced multiple products with camphene and 1,8-cineole as major products, respectively, and AaTPS2 produced a single product, β-myrcene. Although both Mg2+ and Mn2+ were able to support their catalytic activities, altered product spectrum was observed in the presence of Mn2+ for AaTPS2 and AaTPS5. Analysis of extracts of aerial tissues and root of A. annua with gas chromatography-mass spectrometry (GC-MS) detected more than 20 monoterpenes, of which the three enzymes constituted more than 1/3 of the total. Mechanical wounding induced the expression of all three monoterpene synthase genes, and transcript levels of AaTPS5 and AaTPS6 were also elevated after treatments with phytohormones of methyl jasmonate (MeJA), salicylic acid (SA) and gibberellin (GA), suggesting a role of these monoterpene synthases in plant-environment interactions. The three new monoterpene synthases reported here further our understanding of molecular basis of monoterpene biosynthesis and regulation in plant.